Thrombin-induced translocation of GLUT3 glucose transporters in human platelets. - Sorbara, L R (1997)
Platelets derive most of their energy from anaerobic glycolysis; during activation this requirement rises approx. 3-fold. To accommodate the high glucose flux, platelets express extremely high concentrations (155+/-18 pmol/mg of membrane protein) of the most active glucose transporter isoform, GLUT3. Thrombin, a potent platelet activator, was found to stimulate 2-deoxyglucose transport activity 3-5-fold within 10 min at 25 degrees C, with a half-time of 1-2 min. To determine the mechanism underlying the increase in glucose transport activity, an impermeant photolabel, [2-3H]2N-4-(1-azi-2,2,2-trifluoethyl)benzoyl-1,3, -bis-(d-mannose-4-ylozy)-2-propylamine, was used to covalently bind glucose transporters accessible to the extracellular milieu. In response to thrombin, the level of transporter labelling increased 2.7-fold with a half-time of 1-2 min. This suggests a translocation of GLUT3 transporters from an intracellular site to the plasma membrane in a manner analogous to that seen for the translocation of GLUT4 in insulin-stimulated rat adipose cells. To investigate whether a similar signalling pathway was involved in both systems, platelets and adipose cells were exposed to staurosporin and wortmannin, two inhibitors of GLUT4 translocation in adipose cells. Thrombin stimulation of glucose transport activity in platelets was more sensitive to staurosporin inhibition than was insulin-stimulated transport activity in adipose cells, but it was totally insensitive to wortmannin. This indicates that the GLUT3 translocation in platelets is mediated by a protein kinase C not by a phosphatidylinositol 3-kinase mechanism. In support of this contention, the phorbol ester PMA, which specifically activates protein kinase C, fully stimulated glucose transport activity in platelets and was equally sensitive to inhibition by staurosporin. This study provides a cellular mechanism by which platelets enhance their capacity to import glucose to fulfil the increased energy demands associated with activation.